Wakaf Uang: Tingkat Pemahaman Mahasiswa IAIN Padangsidimpuan - Izzah, Nurul; Rambe, Fitriyani; Nanda, Sayang Prima (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2021)
The level of public understanding regarding cash waqf in Indonesia is still low. Even though this waqf has great potential for the welfare of the Indonesian people. This condition has an impact on the benefits obtained from productively managed waqf to be not optimal. This study aims to determine the level of understanding of IAIN Padangsidimpuan students. This research is a quantitative study using primary data. The research sample was 356 people and data were collected by distributing questionnaires to respondents. The data analysis of this study used the univariate test. The results showed that the students of IAIN Padangsidimpuan were categorized as having a sufficient level of understanding. There are 38 percent of students at the level of good understanding, 49 percent of students at the understanding level and 12 percent of students at the low understanding level. Promotion by waqf collection agencies can continue to be carried out to increase public understanding and awareness of cash waqf. Keywords: Cash Waqf, Understanding, Waqf